ESTIMATION OF AGE FROM A STUDY OF THE ERUPTION OF PERMANENT MOLAR TEETH (Journal of Forensic Medicine & Toxicology, 2012)
Age estimation is one of the most frequently performed medico-legal examinations in the living person. The eruption of permanent molar teeth is fairly accurate and relatively simple method of age estimation during the developmental period. The persent study is a cross sectional one caried out on school and college students of Delhi city.
Keywords: Age Estimation; Molar eruption